2005
DOI: 10.1124/jpet.105.086272
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Synergy and Enhanced Murine Brain Penetration of Saquinavir Coadministered with Mefloquine

Abstract: Highly active antiretroviral therapy has substantially improved prognosis in human immunodeficiency virus (HIV). However, the integration of proviral DNA, development of viral resistance, and lack of permeability of drugs into sanctuary sites (e.g., brain and lymphocyte) are major limitations to current regimens. Previous studies have indicated that the antimalarial drug chloroquine (CQ) has antiviral efficacy and a synergism with HIV protease inhibitors. We have screened a panel of antimalarial compounds for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
21
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 33 publications
2
21
1
Order By: Relevance
“…These previous observations showed that several HPIs are effluxed from brain ECs predominantly by the MDR-1 transporter. Neither MRP expression nor MRPassociated efflux function was found to be significantly associated with HPI efflux from mouse brain (33). Hence, approaches to suppress the efflux of therapeutic agents from the human brain had been directed towards a specific blockade of the MDR-1, but not via inhibition of the MRP transporters (32,52,53).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These previous observations showed that several HPIs are effluxed from brain ECs predominantly by the MDR-1 transporter. Neither MRP expression nor MRPassociated efflux function was found to be significantly associated with HPI efflux from mouse brain (33). Hence, approaches to suppress the efflux of therapeutic agents from the human brain had been directed towards a specific blockade of the MDR-1, but not via inhibition of the MRP transporters (32,52,53).…”
Section: Discussionmentioning
confidence: 99%
“…However, the role of different transporters in drug-efflux from the human brain had been derived from indirect evidences, from in vitro cultured brain microvessel ECs from mice (32,33), or rats (50,51). These previous observations showed that several HPIs are effluxed from brain ECs predominantly by the MDR-1 transporter.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HIV PIs and antimalarials, such as mefloquine, are substrates for P glycoprotein (Pgp) efflux pumps; consequently, their pharmacodynamics and pharmacokinetics are modulated by Pgp cellular transport (19,38). Preliminary work on a Pgp in P. falciparum (Pfmdr1) suggests that its amplification is not associated with the synergistic action of PIs with mefloquine (31).…”
mentioning
confidence: 99%
“…The synergy of mefloquine when used with HIV PIs against HIV has been proposed to be due, at least in part, to the ability of the HIV PIs to inhibit mefloquine efflux (14). It is unknown whether the HIV PIs may be able to alter drug efflux in Plasmodium falciparum, and if they can, whether this will have any ramifications for the treatment of multidrug-resistant parasites.…”
mentioning
confidence: 99%